Transcatheter closure of a ruptured sinus of valsalva: a systematic review of the literature - Ayati, Aryan; Toofaninejad, Neda; Hosseinsabet, Ali; Mohammadi, Fatemeh; Hosseini, Kaveh (Frontiers in Cardiovascular Medicine, 2023)
Background: Ruptured sinus of Valsalva (RSOV) is a rare pathology, and current data regarding its symptoms, anatomy, associated pathologies, and appropriate therapeutic approaches are scarce. Transcatheter closure (TCC) has been performed in multiple cases; however, the information on its success rate and complications is limited. Methods: Two independent reviewers performed an advanced search based on inclusion criteria on Scopus, PubMed, and Embase from January 1985 through July 2022. The main search terms were "Sinus of Valsalva", "Rupture/Aneurysm", and "Transcatheter/Catheter/Device".Results: Totally, 1017 relevant articles from the 3 databases were retrieved. After the final review and appraisal, 94 articles describing 407 patients who underwent the TCC of RSOV were included. Males comprised 65% of the studied patients, and the average age was 34.5 years. The total success rate of TCC was 95.6%. Forty-nine patients (12%) developed complications, the most significant of which were sustained residual shunts in 7 patients (1.7%), substantial new onset or progression of aortic insufficiency in 6 (1.5%), and RSOV recurrence in 6 (1.5%). Postinterventional mortality was reported in only 2 patients (0.5%).The present study is the first systematic review of available data regarding the TCC of RSOV principally comprising case series and case reports. Although TCC seems a good option, precise patient selection is mandatory.